2020
DOI: 10.1016/j.njas.2020.100325
|View full text |Cite
|
Sign up to set email alerts
|

The impact of deforestation on collection and domestication of Jernang (Daemonorops spp.) and other NTFPs in southern Sumatra, Indonesia

Abstract: Villagers in southern Sumatra collect a number of NTFPs for cash income and subsistence as a supplement to cultivated crops. Deforestation restricts the availability of NTFPs. The aim of the study was, with point of departure in Jernang, to investigate the transition between collection and cultivation of NTFPs. A village survey encompassing 57 households involved in collection, cultivation and/or trade of Jernang in two villages with high NTFP collection was carried out.The study revealed that more than 20 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Similarly, studies in Benin and Ghana showed that despite overharvesting and extensive commercialisation of Securidaca longipedunculata and Piper guineense, cultivation did not occur or was rare (Van Andel et al, 2015). A study in Sumatra found that only one product (Daemonorops draco) entered cultivation in response to declining wild resources (Schmidt et al, 2020). While our model includes potential explanations for these outcomes, the substantial price changes that some products show require market understanding to explain.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, studies in Benin and Ghana showed that despite overharvesting and extensive commercialisation of Securidaca longipedunculata and Piper guineense, cultivation did not occur or was rare (Van Andel et al, 2015). A study in Sumatra found that only one product (Daemonorops draco) entered cultivation in response to declining wild resources (Schmidt et al, 2020). While our model includes potential explanations for these outcomes, the substantial price changes that some products show require market understanding to explain.…”
Section: Discussionmentioning
confidence: 85%
“…They use them to obtain nutrition, construction material, health ailments andconstruction materials [2,3]. Such products have the ability to nourish the poor, recover their ailments as well as provide subsistence to livelihoods [4]. Thus, NWFPs are the mainstay of livelihoods of the communities relying on forests along with provision of jobs and services [5].…”
Section: Introductionmentioning
confidence: 99%